Benzedeiros e raízeiros e o uso de plantas medicinais em Inaciolândia, Goiás, Brasil - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This study investigated the traditional knowledge and use of medicinal plants by prayer healers (benzedeiros) and herbalists (raizeiros) in Inaciolândia, Goiás, highlighting their specific practices and contributions to folk medicine in the Cerrado biome. To achieve the proposed objectives, a methodological approach was adopted that combined literature review, field research, and ethnobotanical surveys. A total of 180 medicinal plant species native to the Cerrado were cataloged, distributed across 140 genera and 67 botanical families, with emphasis on Fabaceae, Asteraceae, and Bignoniaceae. The results underscore the scarcity of ethnobotanical studies in Goiás and the need to expand knowledge about its biodiversity. Field research identified 39 herbalists and 115 plant species used in traditional treatments, primarily for gastrointestinal, inflammatory, and dermatological conditions, with frequent use of species such as Stryphnodendron adstringens (barbatimão), Phyllanthus niruri (quebra-pedra), and Brosimum gaudichaudii (mama-cadela). Fourteen prayer healers were also identified, mostly women over the age of 60, whose healing practices involve prayers, gestures, and, in some cases, the complementary use of medicinal plants, revealing a strong connection between spirituality, cultural identity, and community health. A decline in interest among younger generations was also observed, threatening the continuity of this traditional knowledge. It is concluded that the appreciation and preservation of popular knowledge associated with medicinal plant-based healing practices are essential for safeguarding the cultural heritage and biodiversity of the Cerrado.
Healers and root healers and the use of medicinal plants in Inaciolândia, Goiás, Brazil
Keywords: Cerrado - Bioma; Conhecimento tradicional; Medicina Popular; Saberes tradicionais; Plantas medicinais; Etnobotânica; Traditional knowledge; Folk medicine; CIENCIAS BIOLOGICAS::BOTANICA